51.4k views
0 votes
Find (gof)(x) when f(x)=sqrt x+3 and g(x)= x^2+2/x

1 Answer

7 votes

Answer:


(gof) (x) =\frac {(x+3)^{(3)/(2)}+2}{\sqrt {x + 3}}

Explanation:

Given : Function
f(x)=\sqrt {x+3} and
g(x)=x^2+(2)/(x)

To find : The value of (gof)(x) ?

Solution :

We know that,


(gof) (x) = g(f (x))

Substituting the values,


(gof) (x) = g(\sqrt {x+3})


(gof) (x) =(\sqrt {x + 3})^2+ \frac {2} {\sqrt {x + 3}}


(gof) (x) =(x + 3) + \frac {2} {\sqrt {x + 3}}


(gof) (x) =\frac {(x+3)(\sqrt {x + 3})+2} {\sqrt {x + 3}}


(gof) (x) =\frac {(x+3)^{(3)/(2)}+2}{\sqrt {x + 3}}

User Eggroll
by
5.0k points